Implementation of DC Motor PID Control On Conveyor for Separating Potato Seeds by Weight - Daniya Sonny Febriyan; Riky Dwi Puriyanto (Association for Scientific Computing Electronics and Engineering (ASCEE), 2021)
Dieng area is a mountainous area, dieng has land with high fertility levels so that they are increasingly high in the agricultural sector, especially potatoes. During the time, the technology for sorting potato seeds was still manual with humans, so it was less effective. The conveyor here is very useful as this device which will later work with loadcell as a weigher, and this device will be driven using a dc motor then the speed stabilization uses the PID algorithm with trial and error methods and this tool is supported using ultrasonic sensors and two servo sorting. This device works with 1 cycle, namely with 1 command with a value of KP 55, KI 20 and KD 0.001. The conveyor movement is quite stable with an average error value of 0.276 load cell with a standard deviation of 0.211877 with an achievement level of 80%.